The effect of the frequency and duration of prostate specific antigen (PSA) measurement on PSA doubling time calculations in men with biochemically recurrent prostate cancer - Paller, CJ (2013)
BACKGROUND: Prostate specific antigen (PSA) doubling time (PSADT) is an attractive intermediate endpoint for assessing novel therapies in biochemically recurrent prostate cancer (BRPC). This study explores whether PSADT calculations are influenced by frequency/duration of PSA measurements, and whether statistical variability leads investigators to find false significant results. METHODS: In retrospective analyses of two BRPC cohorts: Johns Hopkins Hospital (JHH) patients who deferred therapy and placebo patients on a randomized clinical trial (RCT), we calculated changes in PSADT from early measurements to later measurements using subsets of available PSAs for patients with ≥6 and ≥9 PSAs. We simulated hypothetical single-arm trials using randomly selected, 50-patient subsets and simulated two-arm RCTs. RESULTS: JHH cohort (n=205) had median follow-up 58 months, median age 61 years, and median Gleason 7. PSA variability changed with duration of PSA measurement as median within-patient PSADT increases for men with >6 PSAs ranged from 1.0 to 1.4 months by PSA subset while increases for men with ≥9 PSAs ranged from 3.9 to 4.1 months. Frequency of measurement did not change PSA variability as PSADT increase was unchanged when odd values were used instead of all values. Approximately 30% of JHH men experienced >200% increases in PSADT. Up to 62% of 50-patient single-arm simulations detected significant PSADT change, whereas simulated RCTs did not. Results were supported in the RCT placebo cohort; 46% of patients experienced PSADT increases >200%. CONCLUSION: These data suggest that calculated PSADT in BRPC may naturally increase over time in the absence of therapy and may be influenced by duration of PSA follow-up. As a result, single arm trials could show false significant increases despite the lack of active treatment of these patients. Placebo-controlled RCTs including clinical endpoints are recommended to screen novel agents in men with BRPC to mitigate bias because of natural PSADT variability.